Introduction - Massini-Cagliari, Gladis [UNESP]; Berlinck, Rosane Andrade [UNESP]; Rodrigues, Angélica [UNESP] (Springer Nature, 2023)
The introductory chapter presents key notions of linguistic prejudice and language diversity, characterising language prejudice and discrimination as universal problems, before giving an overview of the book’s contents. The main topics addressed in the introduction are definition of language prejudice and language discrimination; brief presentation of the linguistic situation in Brazil (the multiple languages which are spoken/signed in Brazil today and linguistic variation in Brazilian Portuguese); the invisibility of the multiplicity of languages which are spoken in Brazil, in official terms and in the media; and sociolinguistic polarisation in Brazilian Portuguese.
Keywords: Brazil; Language variation; Linguistic diversity; Linguistic prejudice; Signed languages